Chemistry and Biology of HPAs: A Family of Ceramide Trafficking Inhibitors1. Issue 49 (15th September 2016) - Berkeš, Dušan; Daïch, Adam; Santos, Cécile; Ballereau, Stéphanie; Génisson, Yves
Abstract: In 2001, two years before the disclosure of the CERT‐associated Cer transfer machinery, N ‐(3‐hydroxy‐1‐hydroxymethyl‐3‐phenylpropyl)alkanamides (HPAs) were described as the first, and to date unique, family of intracellular Cer trafficking inhibitors. The dodecanamide derivative, HPA‐12, turned out to be a benchmark as a cellular inhibitor of CERT‐mediated de novo sphingomyelin biosynthesis. In only 15 years after its first disclosure, this compound has prompted a growing number of biological and chemical studies. Its initial chemical development closely paralleled the study of the CERT protein. It was only after its structural revision in 2011 that HPA‐12 received broad attention from the synthetic chemistry community, leading to novel analogues with enhanced protein binding. This Minireview aims at presenting an exhaustive report of the syntheses of HPA‐12 and analogues. Biological activities of this CERT inhibitor and structure–activity relationships are also presented to afford a comprehensive overview of the chemistry and biology of the HPA series. Abstract : In 2001, two years before the disclosure of the CERT‐associated Cer transfer machinery, N ‐(3‐hydroxy‐1‐hydroxymethyl‐3‐phenylpropyl)alkanamides (HPAs) were described as the first family of intracellular Cer trafficking inhibitors. The dodecanamide derivative, HPA‐12, turned out to be a benchmark as a cellular inhibitor of CERT‐mediated de novo sphingomyelin biosynthesis. This Minireview aims to present an exhaustive report of the chemistry and biology of the HPA series (see figure).